Spectrum of malignant scalp tumours and its impact on management—a tertiary care cancer centre experience - Bipin T. Varghese; Abinaya R. Nadarajan; Shaji Thomas; Elizabeth Mathew Iype; Nebu Abraham George; Jagathnath Krishna K. M.; Sahya S. Lal; Thara Somanathan (World Journal of Surgical Oncology, 2023)
Abstract Background Tumours on the scalp are diverse and often exhibit site- and histology-specific characteristics. Reconstructing the scalp after oncological resection has always been challenging because of its unique anatomy. Methodology A retrospective review of patients with malignant scalp tumour operated on at a single institution over 10 years was performed. Data were collected and analysed regarding the scalp tumour profile, treatment, and the outcome of these procedures. Results Of the 66 patients in our study, 33 (50%) had SCC. In addition to this, 21% were sarcomas, 17% were appendageal carcinomas, 11% were BCCs, and 1% was neuroendocrine carcinoma. Cortical erosion was observed in 6 patients in the CT imaging, all with SCC histology. Among the eight patients with pathological nodal involvement, three had angiosarcoma, three had SCC, one had appendageal carcinoma, and one had neuroendocrine carcinoma. The mean surgical defect size was 67.4 cm2. The surgical defect was reconstructed with local flaps in 58% of patients and primary closure in 27%. Local and systemic recurrence was noted in 25% of patients. Tumour size more than 6 cm, tumour histology (SCC & sarcoma), unplanned margin-positive excision, and residual disease in re-excision had higher recurrence, even though the p-value was not significant. Conclusion Scalp tumours are heterogeneous in their clinical profiles. Often, its tumour biology and microscopic extent are underestimated. High suspicion, histological diagnosis, and clear surgical margins are all requirements in successfully treating scalp tumours. In order to minimize morbidity and restore an aesthetic and functional outcome, it is critical to use the simplest scalp reconstruction whenever possible.